2012
DOI: 10.1371/journal.pone.0031323
|View full text |Cite
|
Sign up to set email alerts
|

KLC1-ALK: A Novel Fusion in Lung Cancer Identified Using a Formalin-Fixed Paraffin-Embedded Tissue Only

Abstract: The promising results of anaplastic lymphoma kinase (ALK) inhibitors have changed the significance of ALK fusions in several types of cancer. These fusions are no longer mere research targets or diagnostic markers, but they are now directly linked to the therapeutic benefit of patients. However, most available tumor tissues in clinical settings are formalin-fixed and paraffin-embedded (FFPE), and this significantly limits detailed genetic studies in many clinical cases. Although recent technical improvements h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
143
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(146 citation statements)
references
References 43 publications
2
143
1
Order By: Relevance
“…13,14 Other less common 5 0 fusion partners have been described including kinesin family member 5B (KIF5B), TRKfused gene (TFG) and kinesin light chain 1 (KLC1). 8,15,16 ALK rearrangements have been reported to occur at frequencies that range from 0.4 to 15% in NSCLC, 7,17 although some series include selected patient populations likely to be enriched for ALK rearrangements. Most series, however, report an incidence of around 3-4% in unselected NSCLC populations.…”
mentioning
confidence: 99%
“…13,14 Other less common 5 0 fusion partners have been described including kinesin family member 5B (KIF5B), TRKfused gene (TFG) and kinesin light chain 1 (KLC1). 8,15,16 ALK rearrangements have been reported to occur at frequencies that range from 0.4 to 15% in NSCLC, 7,17 although some series include selected patient populations likely to be enriched for ALK rearrangements. Most series, however, report an incidence of around 3-4% in unselected NSCLC populations.…”
mentioning
confidence: 99%
“…Variants v1, v2, v3a and v3b of EML4-ALK fusion gene are the most commonly detected, together accounting for more than 90% of variants in some series (20). Although more uncommon, other ALK fusion partners have been identified as TFG (TRK-fused gene), KIF5B, PTPN3 and KLC1 (21)(22)(23). The different EML4 variants and the further partner genes do not seem to significantly impact on biology and sensitivity of ALK-rearranged malignant cells and tumors to specific inhibitors (24-26) although a putative role in conditioning response to treatments has been reported in vitro (27).…”
Section: Molecular Pathology Of Alk-rearranged Nsclcmentioning
confidence: 99%
“…Also Ou et al recently reported that the emergence of ALK -resistant mutations occurred more commonly in patients with variant 3 EML4-ALK rearrangement than in patients with variant 1 tumors [4]. Other rarer ALK fusions occur such as KIF5B-ALK [5], KLC1-ALK [6], and ALK-PTPN3 [7], but they collectively are less frequent than the ALK-EML4 rearrangement [8], and therefore little is known about their clinical significance with respects to different response to ALK TKIs. In general, patients with ALK -rearranged NSCLC tend to be younger, never smokers, and have lung adenocarcinoma, though rarely patients with other lung cancer histologies have also been found to harbor this mutation [9].…”
Section: Introductionmentioning
confidence: 99%